Un documentaire sur le crime du « Lion d’Or ». Regards croisés sur la valorisation d’un patrimoine judiciaire sensible - Jeanne Barnicaud; Hélène Duffuler-Vialle; Sébastien Landrieux (Criminocorpus)
The documentary L’affaire du crime du ‘Lion d’Or’ (The ‘Lion d’Or’ crime case) was directed by Hervé Colombani. It is based on the work of three researchers (in legal history, the social history of homosexuality and the history of the body) on a judicial archive held by the Archives départementales du Nord: the case file on the murder of Victor Bocquet in Lille in 1925. The long investigation into this crime shook up the world of prostitution in Lille and ended with failure. Thirteen years later, the mystery was solved when the murderer spontaneously confessed. The victim’s homosexuality serves as a background to the case. As part of a reflection on the valorization of dark heritage, this article looks back at the genesis of the project, namely the respective work of the researchers who examined the case from their respective angles, as well as the specific challenges opposed by the documentary and its production.